(3aj GdYbjOIs - (3eLghds
(3ChdgG (B:s
... (3CYfj GdeMd GdeJbhe aj PGJg haYdg Cj dG jMJGL aj PGJg haYdg Edi GdeGOI hgh GdYbd heaGQb aj GdeGOI aj PGfg Ohf aYdg hgh GdfaS Ch ebGQf ddMGdI aEeG Gf jchf eMdG dLhgQ BNQ hgh GdeGOI (B...s
(3BNQgG (B:s
... (3GdeHOYGJ eGdG jchf eSHhbG eGOI heOI cGdaUhd hGdechfGJ eG jchf eSHhbG HGdeGOI dCf GdeOI cGdCadGc hGdeMOKGJ eG jchf eSHhbG HgeG hCeG eG jchf eSSHhbG HGdeOI (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds